2000
DOI: 10.1073/pnas.230453597
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus lacking the hypervariable region 1 of the second envelope protein is infectious and causes acute resolving or persistent infection in chimpanzees

Abstract: Persistent infection with hepatitis C virus (HCV) is among the leading causes of chronic liver disease. Previous studies suggested that genetic variation in hypervariable region 1 (HVR1) of the second envelope protein, possibly in response to host immune pressure, influences the outcome of HCV infection. In the present study, a chimpanzee transfected intrahepatically with RNA transcripts of an infectious HCV clone (pCV-H77C) from which HVR1 was deleted became infected; the ⌬HVR1 virus was subsequently transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 49 publications
3
121
0
Order By: Relevance
“…These infectious clones were used to show that all viral enzyme activities, the p7 gene and the correct genomic 3፱ end are necessary for HCV replication in vivo [54][55][56] . In contrast, the hypervariable N-terminal region of E2 is dispensible 57 . Essentially clonal infections could be initiated from transcribed RNA, providing a well-defined genetic starting point to study virus evolution and immune responses to infection 58 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 97%
See 1 more Smart Citation
“…These infectious clones were used to show that all viral enzyme activities, the p7 gene and the correct genomic 3፱ end are necessary for HCV replication in vivo [54][55][56] . In contrast, the hypervariable N-terminal region of E2 is dispensible 57 . Essentially clonal infections could be initiated from transcribed RNA, providing a well-defined genetic starting point to study virus evolution and immune responses to infection 58 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 97%
“…As this overlaps with the IRES, there is considerable interest in understanding how this region might modulate translation and replication, which are unlikely to occur simultaneously on the same RNA template. The 3፱ NCR has been found to contain a nonessential variable region, a poly-U/UC tract that must be more than 26 nucleotides long, followed by a highly conserved and essential 3፱X domain 55,57,76 . Recently a conserved stem-loop structure within the NS5B coding region, 5BSL3.2, was found to be required for RNA replication 78 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 99%
“…Remarkably, the E2 hypervariable region (HVR1) could be deleted without abrogating infectivity, although the mutant virus replicated poorly and compensating changes in E1 and E2 were selected upon passaging. 15 On the vaccine front, challenge of animals with resolved HCV infection using homologous or heterologous virus has provided evidence for protective immunity. This is an important proof of principle for vaccine development.…”
Section: Animal Models and Cell Culture Systemsmentioning
confidence: 99%
“…With this in mind, the AASLD has launched an annual single topic conference devoted exclusively to viral hepatitis with the intention of bringing together researchers in viral hepatitis to foster progress in this important area. The first of these conferences, held June [15][16] 2001 in Chicago, IL, focused on new, evolving, and future approaches to therapy of hepatitis C.…”
mentioning
confidence: 99%
“…11 Despite a strong amino acid sequence variability, the chemicophysical properties and the conformation of HVR1 have been shown to be well conserved, in agreement with a potential role in virus attachment. 12 However, it has been reported that an HCV clone lacking HVR1 was still infectious in chimpanzee, 13 indicating that HVR1 is not essential for infection in this species. In the hypothesis that SR-BI is a receptor for HCV, these data can only be explained by the existence of an alternative receptor.…”
mentioning
confidence: 99%